A DEDICATED ARCHITECTURE FOR EFFICIENT WEB SERVER TECHNOLOGY - BELLOT, PATRICK; BAUD, LOÏC (Vietnam Journal of Science and Technology, 2012)
ABSTRACTThis article presents SAW, an efficient web server  architecture that can be applied to a wide range of services implementations. SAW can very simply and efficiently implement dedicated Web sites or Web applications. However, it is not intended to act as a full and open Web server. It has been implemented by the authors in Java and also in C/C++ for comparison, testing and evaluation purposes. SAW has been used  by the authors to implement a fully functional Web application related to online conference management. After an overall description of SAW, we give the technical details of its implementation and we provide our conclusions resulting from an analysis of performances, ease of deployment and ease of programming and debugging Web applications.Keywords.Web server, Web services, Web application, Java, C/C++.